Beliefs Toward Social and Cognitive Competences in People with Down Syndrome (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
The inclusion of a person with intellectual disability, such as Down Syndrome (DS), depends not only on the skills of the person himself, but also on the attitude that other persons have to him. Most of the studies that focused on the attitude towards people with DS did not thoroughly investigate the beliefs on the competences of people with DS. Our aim is to identify the commonly held beliefs towards the social and cognitive competences of people with DS. Specifically, we want to verify if there are any differences among the beliefs held by parents of Typical Development (TD) children, parents of people with DS and people without children. A second aim is to evaluate a possible association between the level of knowledge about the Syndrome and related positive beliefs. 363 subjects from 18 to 70 years old (M = 37.56; S.D. = 14.73) were recruited. The sample was divided in three different groups: 1) subjects with TD children; 2) subjects with DS children and 3) subjects without children. An ad hoc self-report questionnaire was administered. Results show that people with Down Syndrome are considered more competent in terms of motor skills, but less competent in social skills. The level of knowledge of the Syndrome correlates positively with beliefs in all competences. There are differences in beliefs between the three groups: parents with DS children have more positive beliefs about all skills, especially as regards the socialization. Knowing the beliefs on the skills of DS people can be very useful, in order to improve inclusiveness of those with DS.